A Chemical Reaction Optimization Approach to Prioritize the Regression Test Cases of Object-Oriented Programs - Sudhir Kumar Mohapatra; Srinivas Prasad (Journal of ICT Research and Applications, 2017)
Regression test case prioritization is used to improve certain performance goals. Limited resources force to choose an effective prioritization technique, which makes an ordering of the test cases so that the most suitable test case will be executed first. Executing regression test cases for a fixed time is all about time aware test case prioritization. Regression test case prioritization using chemical reaction optimization (CRO) for object-oriented programs is proposed in this paper. The effectiveness of the test case ordering was measured using average percentage of faults detected (APFD). Experiments on three object-oriented subject programs involving three different techniques were performed to judge the proposed approach. The empirical results indicate that the algorithm implemented using CRO gives a higher APFD value than the other two techniques.